Telomeres and Telomerase in the Radiation Response: Implications for Instability, Reprograming, and Carcinogenesis - Sishc, Brock J.; Nelson, Christopher B.; McKenna, Miles J.; Battaglia, Christine L. R.; Herndon, Andrea; Idate, Rupa; Liber, Howard L.; Bailey, Susan M. (Frontiers in Oncology, 2015)
Telomeres are nucleoprotein complexes comprised of tandem arrays of repetitive DNA sequence that serve to protect chromosomal termini from inappropriate degradation, as well as to prevent these natural DNA ends from being recognized as broken DNA (double-strand breaks) and triggering of inappropriate DNA damage responses. Preservation of telomere length requires telomerase, the specialized reverse transcriptase capable of maintaining telomere length via template-mediated addition of telomeric repeats onto the ends of newly synthesized chromosomes. Loss of either end-capping function or telomere length maintenance has been associated with genomic instability or senescence in a variety of settings; therefore, telomeres and telomerase have well-established connections to cancer and aging. It has long been recognized that oxidative stress promotes shortening of telomeres, and that telomerase activity is a radiation-inducible function. However, the effects of ionizing radiation (IR) exposure on telomeres per se are much less well understood and appreciated. To gain a deeper understanding of the roles, telomeres and telomerase play in the response of human cells to IRs of different qualities, we tracked changes in telomeric end-capping function, telomere length, and telomerase activity in panels of mammary epithelial and hematopoietic cell lines exposed to low linear energy transfer (LET) gamma(γ)-rays or high LET, high charge, high energy (HZE) particles, delivered either acutely or at low dose rates. In addition to demonstrating that dysfunctional telomeres contribute to IR-induced mutation frequencies and genome instability, we reveal non-canonical roles for telomerase, in that telomerase activity was required for IR-induced enrichment of mammary epithelial putative stem/progenitor cell populations, a finding also suggestive of cellular reprograming. Taken together, the results reported here establish the critical importance of telomeres and telomerase in the radiation response and, as such, have compelling implications not only for accelerated tumor repopulation following radiation therapy but also for carcinogenic potential following low dose exposures as well, including those of relevance to spaceflight-associated galactic cosmic radiations.